Nitrogen Nutrition Improves the Potential of Wheat (Triticum aestivum L.) to Alleviate the Effects of Drought Stress during Vegetative Growth Periods - Abid, Muhammad; Tian, Zhongwei; Ata-Ul-Karim, Syed Tahir; Cui, Yakun; Liu, Yang; Zahoor, Rizwan; Jiang, Dong; Dai, Tingbo (Frontiers in Plant Science, 2016)
Efficient nitrogen (N) nutrition has the potential to alleviate drought stress in crops by maintain-ing metabolic activities even at low tissue water potential. This study was aimed to understand the potential of N to minimize the effects of drought stress applied/occur during tillering (Feekes stage 2) and jointing (Feekes stage 6) growth stages of wheat by observing the regulations and limitations of physiological activities, crop growth rate during drought periods as well as final grain yields at maturity. In present study, pot cultured plants of a wheat cultivar Yangmai-16 were exposed to three water levels (severe stress at 35-40% field capacity (FC), moderate stress at 55-60% FC and well-watered at 75-80% FC) under two N rates (0.24 g and 0.16 g/kg soil). The results showed that the plants under severe drought stress accompanied by low N exhibited highly downregulated photosynthesis, and chlorophyll fluorescence during the drought stress pe-riods, and showed an accelerated grain filling rate with shortened grain filling duration (GFD) at post-anthesis, and reduced grain yields. Severe drought-stressed plants especially at jointing, ex-hibited lower chlorophyll and Rubisco contents, lower efficiency of photosystem II and greater grain yield reductions. In contrast, drought-stressed plants under higher N showed tolerance to drought stress by maintaining higher leaf water potential, chlorophyll and Rubisco content; lower lipid peroxidation associated with higher superoxide dismutase and ascorbate peroxidase activi-ties during drought periods. The plants under higher N showed delayed senescence, increased GFD and lower grain yield reductions. The results of the study suggested that higher N nutrition contributed to drought tolerance in wheat by maintaining higher photosynthetic activities and antioxidative defense system during vegetative growth periods.